Aberration mitigation in high-resolution optical coherence tomography implementing elliptical beam design - Li, Jinhan (2021)
We report an elliptical beam design for aberration mitigation in high-resolution optical coherence tomography (OCT). We polished a large angle on the fiber terminal facet in the sample arm to make a non-rotational symmetric beam with different numerical apertures (NA) for the two axes vertical to the optical axis. By sacrificing the resolution in the out-of-plane transverse direction, the elliptical beam mitigated the aberration introduced by the focusing optics in the OCT system. The elliptical beam with a doubled NA in the in-plane transverse direction promoted the axial field-of-view (FOV) by about 50% and increased the signal back-coupling efficiency by about 25%. We verified the feasibility of the design by imaging the USAF 1951 resolution chart, swine cornea ex vivo, and human skin in vivo. Results show that the proposed method relieves aberration-related problems in high-resolution OCT.